Spiders: Natural controllers of phytophagous insects in rice plantations in Norte de Santander, Colombia - CUEVAS MEDINA, ALFREDO (Revista Colombiana de Entomología, 1994)
The spiders are predators of great importance. They contribute to the consumption of insect pests in the cultivations to decrease the insect populations and to avoid that they exceed the established thresholds. In Norte de Santander, Colombia, there are several species of spiders that help the producers in handling the insects in the rice fields and, for this reason, the existing species were identified, and were established their populational behaviors both in irrigated and dry fields in the different developmental stages of the crop; and also was determined the daily consumption of the three most abundant spiders species in the zone. ln total was found twenty-one species of spiders associated with rice cultivation, of which only twelve were identified as belonging to seven families. The three most common spiders were: Alpaida veniliae (Araneidae), Oxyopes salticus Hentz (Oxyopidae) and Tetragnatha sp. (Tetragnathidae).